1967
DOI: 10.1070/im1967v001n03abeh000573
|View full text |Cite
|
Sign up to set email alerts
|

The Helly Problem and Best Approximation in a Space of Continuous Functions

Abstract: A scheme to generate the twc-mode field entangled states is proposed, based on the Raman interaction of an effective twc-level atom with the pump and Stokes fields. The degree of the entanglement between the two field modes in the entangled states is also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…For X = IR, this was done by A. L. Gaxkavi [1], and for X = C, by the author [2]. G. M. Ustinov [3] announced, for real C(Q, X), assertions similar to the results of the present paper; however, he used a different terminology, different assumptions concerning the space X, and no vector measures.…”
supporting
confidence: 49%
“…For X = IR, this was done by A. L. Gaxkavi [1], and for X = C, by the author [2]. G. M. Ustinov [3] announced, for real C(Q, X), assertions similar to the results of the present paper; however, he used a different terminology, different assumptions concerning the space X, and no vector measures.…”
supporting
confidence: 49%
“…In the real case, a similar theorem was established by Gaxkavi [2] (for other versions, also see [4]). …”
Section: #} Is a Basis In L • I = Q \ Q' = {Tlt2tq} And Qmentioning
confidence: 69%
“…We consider finite-codimensional Chebyshev subspaces in the complex space C(Q), where Q is a compact Hausdorff space, and prove analogs of some theorems established earlier for the real case by Garkavi and Brown (in particular, we characterize such subspaces). It is shown that if the real space C(Q) contains finite-codimensional Chebyshev subspaces, then the same is true of the complex space C(Q) (with the same Q).KEY WORDS: Chebyshev subspace, spaces of continuous functions, best approximation elements.The present paper is closely related to [1][2][3][4] and directly continues the author's paper [5]. A set M in a normed space X is called a proziminal set, or an ezis~ence set, if for any x 6 X the set PMX = {y 6 M : Q'(I) is the set of limit (isolated) points of Q (we assume that Q is infinite); E is the a-algebra of Borel subsets of Q; e and E (possibly, with subscripts) always stand for elements of E; OA is the boundary, .4 the interior, and IAI the caxdinality of a set A; we write v << # on A if a measure v is absolutely continuous with respect to # on a set A (if A = Q, we simply write v << #).…”
mentioning
confidence: 95%
“…The following theorem was established by Garkavi [3] in the real case and by Vlasov [4] for the complex CðQÞ: See also [5,6].…”
mentioning
confidence: 94%